HIGH SCHOOL STUDENTS' PROFESSIONAL SELFDETERMINATION AS A SOCIAL PROBLEM - T. I. Kasyanova; A. V. Maltsev; D. V. Shkurin (Russian State Vocational Pedagogical University, 2018)
Introduction. Nowadays, professional self-determination is recognized to be a significant component of education. In a rapidly changing post-industrial society, professional self-determination turns into the continuous process of forming the professional trajectory by the individual based on the available personal opportunities and requirements. To enhance the effectiveness of this process, a person who is going to enter adulthood needs assistance not only in the choice of profession, but also in search of resources for development and implementation of own educational and professional scenario which is adequate to modern realities and challenges, as well as training in independent use of these resources. In this regard, one of the main priorities of schools is to provide support to students in their professional self-determination and the help in stage-by-stage making decisions on continuation of education and further professionalization.The aim of the present research is an assessment of the state of psycho-pedagogical support for the professional self-determination of students in a modern Russian public school.Methodology and research methods. The methodological framework was the set of competency-based, practice-focused and subject approaches with the position that professional self-determination is a cross-disciplinary continuous social phenomenon. A theoretical part of the research was "The concept of maintenance of professional self-determination of students in the conditions of continuing education". Face-to-face and online questionnaires of teachers and parents were the leading methods of a practical part of the research. The Vortex program was used to process the data obtained using methods of mathematical statistics.Results and scientific novelty. The system of school education does not cope with the vocational-oriented education duty. Based on the review of scientific and sociological sources, the authors identified the problems which do not allow optimizing vocational-oriented work at school level. The authors examined the opinions of teachers and parents of Yekaterinburg school students. The questions dealt with the process of organizing the assistance for professional self-determination of children and teenagers, and the degree of respondents' participation in this process. The authors concluded that most of teachers and parents suggest that vocational-oriented events should be held regularly since the 7-8th grades. The overwhelming number of respondents believe that acquisition of knowledge about the world of the professions and skills is additional, but it can be involved into the study load for the fullest self-realization of a child in the future. From the point of view of parents, the most popular professions among school students were revealed and ranged. The respondents' estimates of a contribution to professional selfdetermination of pupils of additional professional education, socially useful labour and volunteering were analyzed. Factors and prerequisites of effective vocationaloriented work were highlighted. In particular, vocational-oriented work can be successful only in case parents of students are engaged members of the process. Practical significance. The materials, conclusions and recommendations of the research can be used to enhance vocational-oriented work among teenagers and students.